Sumber belajar matematika melalui eksplorasi etnomatematika pada kue mangkuak basayak - Rahmi, Fathur; Iltavia (Karoteh Utama, 2024)
This study is an exploratory research aimed at uncovering the relationship between mathematical concepts and the traditional Mangkuak Basayak cake, a distinctive delicacy from West Sumatra. The primary focus of this research is to explore ethnomathematical elements in community activities, particularly in the process of making and shaping the cake, which has the potential to become a contextual source for mathematics learning. Using ethnographic methods, data collection involved direct observation, in-depth interviews with cultural practitioners, documentation, and field notes adhering to the principles of authentic ethnographic description. The findings indicate that the process of making Mangkuak Basayak involves various mathematical concepts, such as proportional comparisons of ingredients, measurements, and geometric shapes visible in the cake's structure. These findings affirm that local culture can be integrated into mathematics education to enhance students' understanding through contextual approaches relevant to daily life.